Penerapan Role Playing Pada Pembelajaran Akidah Akhlak Guna Peningkatan Prestasi Belajar Siswa Kelas V MI Muh Nogosari Giri Mulyo Progo Tahun Pelajaran 2021/2022 - Suyono Suyono (Pedir Research Institute, 2022)
The large number of students whose learning achievement is lacking in learning is due, in part, to the fact that the learning process so far has not actively involved students, so that student learning achievement is far from what was expected. playing in Grade V MI Muh Nogosari Giri Mulyo Kulon Progo Students for the 2021/2022 Academic Year. This research is a Classroom Action Research which consists of two cycles and involves four components namely: Planning (plan), Action (action), Observation (observation), Reflection (reflection). The subjects in this study were Class V MI Muh Nogosari Giri Mulyo Kulon Progo Students for the Academic Year 2021/2022, a total of 14 students. Methods of data collection using observation and documentation. The collected data were analyzed using descriptive statistical methods. From the results of the study it was found that the role playing method in learning the Akidah Akhlakh was able to improve the learning achievement of Class V MI Muh Nogosari Giri Mulyo Kulon Progo Academic Year 2021/2022. In cycle I the learning achievement of the Akidah Akhlakh students experienced an increase after the implementation of the role playing strategy. This can be seen from the percentage of classical learning completeness, namely in the first cycle of 57%, and in the second cycle of 83.78%. The results of this research can be used as reference material for us to improve student achievement.